Erdös-Ko-Radojev izrek - Silovšek, Tjaž (Matrika, 2021)
The article presents the Erdös-Ko-Rado Theorem from the area of extremal combinatorics. The theorem establishes the upper limit for the size of family of sets with certain properties. At the end of the paper it is also shown how to construct our families in order to reach the upper limit, and when the upper limit can be reached in only one way.
Keywords: combinatorics; ekstremalna kombinatorika; extremal combinatorics; kombinatorika